Effectiveness of different cleaning agents on the adherence of Candida albicans to acrylic denture base resin - ÖZKAN, YASEMİN (WILEY, 2011)
doi: 10.1111/j.1741-2358.2010.00379.x ? Effectiveness of different cleaning agents on the adherence of Candida albicans to acrylic denture base resin
Keywords: cleaning agents; C; albicans; complete dentures; ORAL HYGIENE; CHLORINE DIOXIDE; STOMATITIS; EFFICACY; SURFACES; CHLORHEXIDINE; MOUTHRINSE; ADHESION; PLAQUE